Sustainability Efforts in the Hotel Industry: A Systematic Literature Review - Adams, Shani; Kageyama, Yoshimasa; Barreda, Albert A (Journal of Tourism Management Research, 2022)
Many definitions have been offered for the term “sustainability” within the hotel industry, and because of this, many business owners have been skeptical of what the term really means, and all that it encompasses; this uncertainty has, unfortunately, rendered them hesitant to initiate any efforts towards accepting it within their hotel doors and within their business plan. The aim of this research is to provide a sense of a road map to sustainability efforts within the Hotel Industry (all around the world); provide an array of options for new innovative sustainability efforts for hoteliers; and a look into what sustainability efforts actually exists in the industry today. The author statistically analyzed a total of 45 articles and journals and narrowed them down to twenty-seven which were most relevant to the research topic. The results show that not only is sustainability in the Hotel Industry very relevant, but that there are also many creative ways (through construction, technology, etc.) in which hoteliers are placing sustainable efforts at the forefront of their business strategies, evidenced in the growth of their customer base and customer satisfaction, reduction of their carbon footprint, as well as an increase in their overall corporate rating amongst hotels globally. The results of the review also identified the gap in the existing literature relating to sustainability in hotels.